The Influence of Sports Celebrity Endorsement Towards the Intention to Visit Ecotourism Destination - Kong, Lyn Huei (2015)
Given that Pahang, being the largest state in Peninsula Malaysia is targeting more tourists visit, it is proposed to use advertisement featuring sports celebrities to increase potential consumers’ awareness and to spark their interest to travel to Taman Negara National Park. This study has investigated the effectiveness of using of celebrity endorsement especially using sports celebrities (national and international) to promote ecotourism in Malaysia’s National Park. Besides, this study also looked into which endorser (local or foreign sports celebrity) had more celebrity credibility in a print advertisement to influence consumer visit intention pertaining to ecotourism. Additionally, this study would help to identify Malaysian consumers’ environmental values (consisting of eco-centrism, conservation values and sustainable tourism) which play an important role to influence attitude toward the ecotourism destination. A review of existing literature relating to celebrity endorsement and ecotourism were made in order to grasp some background knowledge on this research area. After that, Chapter 3 Research Methodology explained the data collection method i.e. self-administrated questionnaire. There were three sets of surveys used which each having stimulus material i.e. advertisement created – ad without celebrity; ad with local sport figure; and ad with international sport figure which were randomly given to the samples. Convenience sampling was used yet with an endeavour to attain a balanced and heterogeneous sample. Followed to that, 305 questionnaires with collected data were presented in Chapter 4 titled Data Analysis and Finding after data screening. For data analysis, statistical analysis employed were descriptive analysis, measurement of central tendencies, independent sample t-test, correlation analysis and multiple regression analysis. Based on the conceptual framework, there were 14 hypotheses. After conducting respective tests, eight hypotheses were accepted and six were rejected. Overall, the conceptual model was valid as examined using regression analysis. In Chapter 5 - Discussion, recommendation and conclusion, the results were discussed with the support from literature review. Lastly, the research was completed with a conclusion and recommendations as well as appendices that were attached with the necessary documents for this study.